A diligent man - Agbaeze, Theophilus Ubendu (Abuja, Nigeria : Theophilus Ubendu Agbaeze, 2018)
The book x-rays the strategic roadmap to success, prosperity, fame and power which the diligent man will walk to be noticed on the social radar.
Includes bibliographical references.
oif 23/01/2020
Loans
Keywords: Diligence